Synthesis of chiral N-phosphinyl α-imino esters and their application in asymmetric synthesis of α-amino esters by reduction - Xiong, Yiwen; Mei, Haibo; Wu, Lingmin; Han, Jianlin; Pan, Yi; Li, Guigen (Beilstein Journal of Organic Chemistry, 2014)
A variety of chiral N-phosphinyl α-imino esters have been synthesized for the first time from ketoesters and phosphinylamide, which were then reduced by L-selectride to give the corresponding N-phosphinyl-protected α-amino esters. The reduction proceeded very well with excellent chemical yields (88–98%) as well as high diastereoselectivities (96:4 to 99:1). Some of these products could be obtained without column chromatography and recrystallization. The chiral phosphinyl auxiliary could be easily cleaved under acidic conditions.
Keywords: α-amino ester; α-imino ester; group-assisted purification; phosphinyl auxiliary; reduction